Perceptions on Climate Change and Religion: A Christian Theological-Functionalist Study - Khumalo, Mandla; Dunn, Nonhlanhla (Religion and Policy Journal, 2025)
Research Problem: Climate change requires a communal response including from a religious perspective. There is an increasing debate among scholars about the role of religion in mitigating climate change and whether religion can influence environmental policies. There is also a need to explore perceptions from religious groups and understand their viewpoints on the climate change challenge.  . Research Purposes: This study examines perceptions and the role of religion in relation to climate change. It also assesses perceived views from religious groups on how climate change can be addressed. The study argues that while it is not conclusive whether religious identity can expedite the control and acceptance of anthropogenic and scientific climate change, perhaps it can help bring fresh insights. What are perceptions towards climate change and religion? What is the role of religious institutions in the drive to combat climate change? These are the two questions the study tried to contribute answers to. This study also aims to get insights on the perceived eschatology theory as propagated by religion. Research Methods: Data were derived from 35 participants from the Christian faith. Participants were between the ages of 18 – 56 in range.  Following a theological and functionalist framework data was analysed using thematic approach. The data was transcribed and coded to produce themes. Themes were categorized through grouping similar codes. Results and Discussion: The study revealed that Christians perceive religion as important in addressing climate change effects. The potential for religion to influence climate change policies remain unfulfilled. Christian views identified climate change as anthropogenic, divine and eschatological. While scientific models were not rejected, the results revealed that scientific models separate of spirituality bring temporal solutions. Research Implications and Contributions: At the policy level, governments should consider religion and how religious insights can be infused into state policies. Church leaders must continue to create climate change awareness in their meetings.